Pengembangan Komposisi Terbaik Bahan Baku Olahan Sabun Organik Daun Kersen (Sodasen) Sebagai Bodycare - Anggraini, Riana; Yernisa, Yernisa; Muryanika, Rince; Nurmansah, Rahmad; Airlangga, Andres Arya (Jurnal Pengabdian Masyarakat Pinang Masak, 2024)
Kersen leaves can be processed into bodycare in the form of liquid soap called Sodasen (Kersen Leaf Organic Soap). This product in the form of organic soap made from cherry leaves (Muntingia calabura) not only prioritizes skin health, but also offers an entrepreneurial concept based on sustainability and concern for the environment. The making of Sodasen has been carried out by the Entrepreneurship Student Creativity Program Team (PKM-K) of Forestry Study Program Students with the guidance of one of the service team lecturers. However, there are still obstacles in developing the best composition to produce marketable Sodasen. Based on this, it is necessary to conduct training and assistance to partners (PKM-K Team) to find the best formula or composition production technology in making Sodasen soap and carry out SNI standard soap quality test testing so that Sodasen soap products can be in demand by the market. The results of liquid soap quality testing obtained the best Sodasen liquid soap composition at a concentration of 10% meeting SNI standards on liquid soap quality.